An efficient implementation of credit card fraud detection using CatBoost algorithm - Suryanarayana, Vadhri; Maddileti, Kuruva; Satyanarayana, Dune; Jyothi, R Leela; Sreekanth, Kavuri; Mande, Praveen; Miriyala, Raghava Naidu; Sudhakar, Oggi (Institute of Advanced Engineering and Science, 2025)
Transaction fraud has grown to be an important issue in worldwide, banking and commerce security is easier access to trade information. Every day, there are more and more incidents of transaction fraud, which causes large financial losses for both consumers and financial professionals. The ability to identify transaction fraud is getting closer to reality due to improvements in computer science's machine learning (ML) and data mining areas. So, one of them that is becoming dangerous is credit card fraud (CCF). Millions of people are experiencing financial loss and identity theft as a result of these malicious operations. The CCF of many illegal activities that fraudsters are always using new methods to carry out. One major problem facing financial services sector is CCF. To overcome this, categorical boosting (CatBoost) algorithm is explained as a solution to these problems. Fraud or fraudulent transactions are identified using this effective CatBoost algorithm implementation for identification of CCF. Thus, in terms of accuracy, precision, and detection rate this method gives better performance.